The Concept of Hadhanah from the Perspective of the Syafi'i Mazhab and Its Implementation in the Decision of the Syar'iyah Court of Banda Aceh City Number 314/Pdt G/2017/MS Bna: Konsep Hadhanah Perspektif Mazhab Syafi'i dan Implementasinya dalam Putusan Mahkamah Syar'iyah Kota Banda Aceh Nomor 314/Pdt G/2017/MS Bna - A. Gani, Burhanuddin; Mughnia, Aja (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2021)
One of the themes of Islamic family law is haḍānah. In the Shafi'i school, the right of haḍānah is assigned to the mother. However, if they do not meet the qualifications and requirements for parenting, they are transferred to their maternal grandmother, paternal grandmother, mother's sister, maternal aunt, daughter of mother's brother, daughter of mother's sister, paternal aunt, and father. However, in the decision of MS Banda Aceh No. 314/Pdt.G/2017/Ms.Bna, the right of haḍānah is actually given to the father, when the mother does not have the qualifications to raise children. For this reason, the problem of this research is what is the basis for the consideration of the judges of the Banda Aceh Syar'iyah Court in deciding the haḍānah lawsuit Number 314/Pdt.G/2017/MS.Bna, and how the implementation of the haḍānah concept in the Syafi'i school is seen based on the Decision of the Sharia Court Banda Aceh Number 314/Pdt.G/2017/MS.Bna. This research is included in library research and qualitative approach, with the type of descriptive-analysis. The results of the study indicate that the basis for the consideration of the MS Banda Aceh panel of judges refers to legal facts and witness statements. The panel of judges considered that the child's life was more secure and the benefit of the child was given to the defendant (father) rather than the plaintiff (mother). The implementation of the concept of aḍānah in the decision is not in accordance with the provisions of the order of hadhanah rights in the Shafi'i school. In the Shafi'i school, if the mother does not meet the qualifications for the hadhanah right, then it turns to her maternal grandmother, paternal grandmother, mother's sister, maternal aunt, daughter of mother's brother, daughter of mother's sister, aunt from the father's side. After that, it was given to my father. While in the decision, hadhanah rights are given to the father after the mother does not meet the requirements hadhanah.